Hearing Improvement after Radiation Therapy for a Facial Nerve Schwannoma: Report of a Case and Review of Literature - Pecorari, Isabella L.; Ghosh, Sayak R.; Moskowitz, Howard S.; Agarwal, Vijay (Journal of Neurological Surgery Reports, 2024)
Introduction While facial nerve schwannomas are considered benign, they can impart various significant clinical effects due to pressure on nearby cerebrovascular structures within the cerebellopontine angle (CPA). Although surgical resection and/or radiation therapy often provide definitive treatment of such tumors, posttreatment hearing loss is a common finding. In this report, we present the case of a patient with a facial nerve schwannoma successfully treated with radiotherapy with resultant hearing improvement, an extremely rare clinical finding.Case Presentation A 63-year-old woman presented with a 1-year history of progressively worsening hearing loss and tinnitus. Brain imaging demonstrated an enhancing lesion of the right CPA measuring 2.7 × 2.1 × 3.1 cm. Pretreatment audiometry evaluation revealed sensorineural hearing loss in the right ear with a pure-tone average (PTA) of 74 dB, speech threshold (ST) of 75 dB, and speech discrimination (SD) of 0%. The patient proceeded with attempted surgical resection, aborted due to significant facial nerve stimulation, and ultimately underwent radiation therapy (50.4 Gy, 28 fractions). At the 1-year follow-up visit, the patient reports subjective hearing loss resolution with PTA of 34 dB, 30 dB ST, and 88% SD on audiological evaluation.Conclusion Although radiation therapy for schwannomas within the CPA has historically been associated with hearing loss, fractionated stereotactic radiotherapy (FSRT) may provide improved clinical outcomes compared with high-dose radiosurgery. Given the effectiveness of this treatment modality and improved quality of life offered to patients over surgery, FSRT may be considered an initial management option for patients with facial nerve schwannomas.
Keywords: facial nerve schwannoma; hearing improvement; radiation therapy; CPA mass